Eumycetoma causative agents are inhibited in vitro by luliconazole, lanoconazole and ravuconazole. Issue 6 (6th May 2022) - Nyuykonge, Bertrand; Lim, Wilson; van Amelsvoort, Lukas; Bonifaz, Alexandro; Fahal, Ahmed; Badali, Hamid; Abastabar, Mahdi; Verbon, Annelies; van de Sande, Wendy
Abstract: Introduction: Eumycetoma is a subcutaneous mutilating disease that can be caused by many different fungi. Current treatment consists of prolonged itraconazole administration in combination with surgery. In many centres, due to their slow growth rate, the treatment for eumycetoma is often started before the causative agent is identified. This harbours the risk that the causative fungus is not susceptible to the given empirical therapy. In the open‐source drug program MycetOS, ravuconazole and luliconazole were promising antifungal agents that were able to inhibit the growth of Madurella mycetomatis, the most common causative agent of mycetoma. However, it is currently not known whether these drugs inhibit the growth of other eumycetoma causative agents. Materials and methods: Here, we determined the in vitro activity of luliconazole, lanoconazole and ravuconazole against commonly encountered eumycetoma causative agents. MICs were determined for lanoconazole, luliconazole and ravuconazole against 37 fungal isolates which included Madurella species, Falciformispora senegalensis, Medicopsis romeroi and Trematosphaeria grisea and compared to those of itraconazole. Results: Ravuconazole, luliconazole and lanoconazole showed high activity against all eumycetoma causative agents tested with median minimal inhibitory concentrations (MICs) ranging from 0.008–2 µg/ml, 0.001–0.064 µg/ml and 0.001–0.064 µg/ml, respectively. Even Ma .  fahalii and Me. romeroi, which are not inhibited in growth by itraconazole at a concentration of 4 µg/ml, were inhibited by these azoles. Conclusion: The commonly encountered eumycetoma causative agents are inhibited by lanoconazole, luliconazole and ravuconazole. These drugs are promising candidates for further evaluation as potential treatment for eumycetoma.